2021
DOI: 10.3389/fped.2021.625031
|View full text |Cite
|
Sign up to set email alerts
|

Close Association Between Platelet Biogenesis and Alveolarization of the Developing Lung

Abstract: Bronchopulmonary dysplasia (BPD) is a neonatal chronic lung disease characterized by an arrest in alveolar and vascular development. BPD is secondary to lung immaturity, ventilator-induced lung injury, and exposure to hyperoxia in extremely premature infants, leading to a lifelong impairment of lung function. Recent studies indicate that the lung plays an important role in platelet biogenesis. However, the dynamic change of platelet production during lung development and BPD pathogenesis remains to be elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Recently, the concept that megakaryopoiesis occurs in the lung parenchyma with significant contribution of the lungs in platelet biogenesis has emerged (74)(75)(76). There is a close association between platelet biogenesis and alveolarization of the lung (77,78), and hypoxia-induced thrombocytopenia associated with reduction of lung megakaryocytes and impaired generation of platelets in the lungs (79). The SARS-CoV-2 virus elicited up-regulation of megakaryocyte progenitors and elevated circulating megakaryocytes in blood in severe COVID-19 (80,81), hypothetically through infection of early megakaryocyte progenitors.…”
Section: Platelet Changesmentioning
confidence: 99%
“…Recently, the concept that megakaryopoiesis occurs in the lung parenchyma with significant contribution of the lungs in platelet biogenesis has emerged (74)(75)(76). There is a close association between platelet biogenesis and alveolarization of the lung (77,78), and hypoxia-induced thrombocytopenia associated with reduction of lung megakaryocytes and impaired generation of platelets in the lungs (79). The SARS-CoV-2 virus elicited up-regulation of megakaryocyte progenitors and elevated circulating megakaryocytes in blood in severe COVID-19 (80,81), hypothetically through infection of early megakaryocyte progenitors.…”
Section: Platelet Changesmentioning
confidence: 99%
“…This increase in platelet biogenesis stabilizes at approximately day 20 of life in rats, which coincides with the process of postnatal alveolarization. These findings suggest a role for platelets in alveolarization in the developing lung ( 12 ). Furthermore, we also observed impaired platelet biogenesis in both BPD infants and rats with experimental BPD ( 12 ).…”
Section: Introductionmentioning
confidence: 75%
“…We have previously shown that platelets are reduced in infants and rats with BPD ( 12 ). In this study, we demonstrated that platelet depletion in mice led to alveolar simplification with enlarged alveoli, similar to experimental BPD ( Figures 2E,F ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this finding, Sallmon et al ( 9) also reported an increase in platelet count after the first course of cyclooxygenase inhibitor (COXI) cycle in both success and failed ductus closure. This could be partially attributed to the physiological increase of platelet count in the postnatal life of premature infants (32). Furthermore, ibuprofen might interfere with platelet function as the authors and other researchers suggested (9,33).…”
Section: Discussionmentioning
confidence: 95%